2001
DOI: 10.1200/jco.2001.19.20.4065
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Pharmacokinetic Model for Paclitaxel

Abstract: Earlier PK models for paclitaxel have been empirical. This study shows that a mechanistic model can be used to describe the nonlinear PK of paclitaxel. There is an indication that the PK/PD relationship is not the same for unbound and total plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 15 publications
7
93
2
Order By: Relevance
“…The pharmacokinetics of BMS-184476 in combination with carboplatin in this study appeared linear as was observed for BMS-18476 as a single agent (Plummer et al, 2002). This is in contrast to the nonlinear pharmacokinetic behaviour of paclitaxel (Gibaldi and Perrier, 1982;Henningsson et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…The pharmacokinetics of BMS-184476 in combination with carboplatin in this study appeared linear as was observed for BMS-18476 as a single agent (Plummer et al, 2002). This is in contrast to the nonlinear pharmacokinetic behaviour of paclitaxel (Gibaldi and Perrier, 1982;Henningsson et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, CrEL significantly alters the pharmacokinetics of paclitaxel (2)(3)(4)(5). The pharmacokinetic behavior of paclitaxel has been proposed to be distinctly nonlinear because the drug is trapped in micelles, making it less available for tissue distribution, metabolism, and biliary excretion, whereas CrEL-free paclitaxel appears to be linear (6,7). Moreover, paclitaxel must be prepared in either a glass bottle or in non-polyvinyl chloride infusion systems with in-line filtration to prevent precipitation from CrEL and solvent (8).…”
Section: Introductionmentioning
confidence: 99%
“…Later, the formulation vehicle of paclitaxel, Cremophor EL, was reported to be the cause of the (apparent) nonlinear plasma behavior of paclitaxel, probably by entrapment of paclitaxel into micelles (3 -7). Generally, substantial interpatient variability of paclitaxel pharmacokinetic variables has been noted (8).…”
mentioning
confidence: 99%